Drivers of changing crops and cropping patterns in the different elevation zones of middle mountain, Nepal - Chapagain, Prem Sagar; Ghimire, Payaswini; Yan, Jianzhong; Cheng, Xian; Liu, Linshan; Zhang, Yili (Geographical Journal of Nepal, 2022)
Studies on rural livelihood, agriculture patterns from different parts of Nepal have mentioned the introduction of new crops from different pocket areas of the country primarily resulted due to climate change and market development. However, these studies have lacked scholarship on how the changes occur in rural areas and how rural households have adopted the changes are least focused. Based on the field surveys using questionnaires, interviews, FGD, analysis of climate data, and map data, this paper aims to fulfill the aforementioned gap based on the study from three elevation zones. It shows a wider adoption of different new crops and vegetables which are varied by elevation zones and by the cultural groups living there. The detailed analysis of various events and underlying processes concludes that out-migration and off-farm employment, infrastructure development and increasing connectivity, climate change, access to market, and changing food habits are the major drivers of the changes. These drivers began to play their roles at different times, and different scales in different zones, and finally their complex interplay resulted changes in the rural agricultural landscape.